The Role Of Digital Learning Media In Motivating Elementary School Students' Learning - Murtiani; Lia Fitriyani; Indah Sriwahyuni; Eydel ways Putri Anisa (EDUJAVARE: International Journal of Educational Research, 2026)
The development of digital technology has changed many aspects of education, including at the elementary school level. A common problem in classrooms is low student learning motivation due to teaching methods that lack student engagement. This study aims to examine the role of digital learning media in improving elementary school students' learning motivation using a literature review method. The data sources used were twelve national scientific journal articles published between 2023 and 2026, which discussed various types of digital learning media, such as digital interactive boards or smartboards, learning videos, PowerPoint presentations, and the interactive quiz application Quizizz. Data were analyzed descriptively and qualitatively using thematic analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results show that digital learning media has a positive impact on elementary school students' learning motivation, both internally and externally, by increasing attention, active engagement, self-confidence, and creating a pleasant learning atmosphere. However, its effectiveness still depends on the limitations of technological infrastructure, teachers' digital readiness and skills, and the risk of dependency and overstimulation in students. This study recommends continued teacher training and equitable distribution of technological infrastructure to optimize the use of digital media in learning.